The Effect of Entrepreneurship Orientation and Product Innovation on Axa Mandiri Insurance Marketing Performance (Case Study of AXA Mandiri Customers in Palopo City) - Henny Apridasanti; Muhammad Aqsa; M. Risal (Jurnal Mantik, 2022)
The discussion in this study is focused on the marketing performance of AXA Mandiri's insurance. Which is located in the city of Palopo – South Sulawesi. With a total of 89 data from 89 respondents. The analytical tool used in this research is multiple regression. The results show that entrepreneurial orientation has a positive and significant impact on marketing performance. Likewise, product innovation has a significant and positive effect on marketing performance.